Estudo de polimorfismos (GERMLINE) no gene egfr (receptor do fator de crescimento epidermal) e possíveis associações com a resposta citotóxica em fibroblastos tratados com inibidores de tirosina quinase - Montenegro, Raquel Carvalho (2006)
Only a small number of cancer patients benefit from therapy with EGFR inhibitors. It is therefore important to understand the mechanism of action of these drugs and to find predictive markers for drug response to guide the selection of patients who can benefits from these drugs. Although somatic mutations and gene amplification have been correlated with the efficacy of EGFR-targeting therapy, cancer cells and/or patients with normal EGFR expression are also sensitive to these drugs. We then aim to further understand the mechanism underlying the predisposition to sensitivity to EGFR inhibitors in germline cells. We chose 70 human normal fibroblasts cell lines as an in vitro model. Cytotoxicity studies were performed on these cells using two EGFR inhibitors, tarceva (T), gefitinib (G) and AG1478 (AG). Cells were incubated with serial concentrations of the drugs (10, 20, 40 and 60 µM for T and G and 5, 10, 15 and 20 µM for AG) dissolved in DMSO. Growth inhibition was measured by Alamar Blue. Four polymorphisms, -216G/T, R497K, 787C/T and intron 1 (CA)n, were genotyped in these cells. EGFR expression was measured with real-time PCR. There was considerable variability in drug response in a dose-dependent manner among these cells. No working concentration were found to be toxic for T. The other two drugs behaved quite differently. The fibroblasts had a much more variable response to G (mean of coefficient of variance of survival rates under all 4 concentrations, 61%) when compared to the response to AG (26%). Drug response was not correlated with EGFR expression. A significant correlation was observed between the R497K polymorphism and the survival rate of cells treated with AG at 5 μM (p<0.01) and 10 µM (p<0.05) with higher growth inhibition in K allele-carriers. No correlation was observed between any of the four EGFR polymorphisms and G cytotoxicity. These observations suggest that the cytotoxic effects of G and AG are due to different mechanisms, and that other genes such as transporters may also contribute to drug response. The R497K polymorphism may be useful as a predictive marker for response to AG and/or similar agents. Also, pathway studies should be done to clarifyed the relationship between response and cutaneous rash in patients treated with tirosine kinase inhibitors.